2017
DOI: 10.1001/jamasurg.2017.2181
|View full text |Cite|
|
Sign up to set email alerts
|

Factors Associated With Underestimation of Invasive Cancer in Patients With Ductal Carcinoma In Situ

Abstract: IMPORTANCE Recent recognition of the overdiagnosis and overtreatment of ductal carcinoma in situ (DCIS) detected by mammography has led to the development of clinical trials randomizing women with non-high-grade DCIS to active surveillance, defined as imaging surveillance with or without endocrine therapy, vs standard surgical care.OBJECTIVE To determine the factors associated with underestimation of invasive cancer in patients with a clinical diagnosis of non-high-grade DCIS that would preclude active surveil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 31 publications
(112 reference statements)
5
25
0
Order By: Relevance
“…The underestimation rate of 24.4% found in our study was similar to that reported in the literature. 21 , 22 During the study period, vacuum biopsy (mammotomy), which uses larger caliber needles (9 gauge) and enables greater precision, was not available at the clinic. The high cost of the mammotomy needle device limits access to this technique in Brazilian public institutions.…”
Section: Discussionmentioning
confidence: 99%
“…The underestimation rate of 24.4% found in our study was similar to that reported in the literature. 21 , 22 During the study period, vacuum biopsy (mammotomy), which uses larger caliber needles (9 gauge) and enables greater precision, was not available at the clinic. The high cost of the mammotomy needle device limits access to this technique in Brazilian public institutions.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main concerns HCPs expressed in this study was around the uncertainty in accurately diagnosing DCIS based on imaging and core biopsy alone. Studies have estimated that diagnostic core biopsies in non-high grade DCIS underestimate invasive cancer by 8–22% [ [31] , [32] , [33] ]. HCPs explained that surgery and the associated full pathology ameliorates uncertainty around the extent and true features of the DCIS.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, overdiagnosis and overtreatment are emerging issues in DCIS patients diagnosed via breast cancer screening. Therefore, in patients diagnosed with DCIS through biopsy, prediction of invasive cancer seems essential for selecting breast cancer treatment options (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have been carried out to define the clinicopathological characteristics associated with an upgrade to invasive cancer in patients preoperatively diagnosed with DCIS (5)(6)(7)(9)(10)(11)(12)(13)(14)(15). The possible predictors include the patient's age, palpability, tumor size, tumor grade, biopsy method, and some immunohistochemi-Copyright © 2021, Author(s).…”
Section: Introductionmentioning
confidence: 99%